Cyclic response sensitivity of energy dissipating steel plate fuses. (February 2020) - Siar Mahmood Shah, Ahmad; Moradi, Saber
Abstract: Steel plate devices are commonly used for the seismic energy dissipation and damage mitigation of structures. Particularly, butterfly-shaped steel plate fuses are essential components in controlled rocking frames, which have been shown as promising self-centering systems for minimizing financial losses due to repair costs and downtime in strong earthquakes. The cyclic behavior of a steel plate fuse varies depending on design factors related to its geometry and material. This paper aims at assessing the effect of seven factors on the cyclic response of steel plate fuses. These factors include the fuse length, mid-width, end-width, thickness, band zone length, fuse yield strength, and modulus of elasticity. Detailed finite element models are first developed and validated against past experimental test results. A design of experiment method is used to statistically evaluate the effects of the design factors and their interactions on the cyclic response characteristics of steel plate fuses in terms of initial stiffness, yield strength, ultimate stiffness, effective damping, maximum strength, and ductility. The results show that the most significant effects are the fuse end-width, thickness, and length.